Analysis of particle size and XRD in ZnO-based varistor - Noor Azira, Mohd Noor; Mohabattul Zaman B. S., NS Bukhari, Prof Madya; Muhammad Asri, Idris; Noor Mariamadzliza, Mohd Nan (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.